Simulation of CNC Milling on Chain Adjuster Design Using Fusion 360 to Enhance Process Time Efficiency - Ikhwan Praditya Mirwany; Safarudin Ramdhani (Universitas Suryakancana, 2026)
The digitalization of physical fluid phenomena in pump performance teaching media remains a significant challenge in the development of online and laboratory-based learning tools. This study aims to develop a Human Machine Interface (HMI) based device as a teaching aid to support pump performance practicum for students. The system is designed to provide informative, real time, and responsive visualizations associated with valve opening adjustments and motor shaft rotation. The development process follows the waterfall model, which includes requirement analysis, system design, implementation, and verification. The resulting HMI interface dashboard demonstrates interactive capabilities, enabling users to monitor and control system parameters effectively. The system responds dynamically to operational changes and displays variations in key parameters such as pressure and fluid flow rate in real time. The implementation of this HMI based learning media is expected to enhance students’ understanding of fundamental pump performance concepts by providing a more engaging and intuitive learning experience. Through dynamic visualization and interactive control features, the system bridges the gap between theoretical knowledge and practical application during laboratory sessions.